Fosfomycin therapeutic drug monitoring in real-life: development and validation of a LC-MS/MS method on plasma samples. (31st January 2022) - Baldelli, Sara; Cerea, Matteo; Mangioni, Davide; Alagna, Laura; Muscatello, Antonio; Bandera, Alessandra; Cattaneo, Dario
Abstract: Individualization of fosfomycin dosing based on therapeutic drug monitoring (TDM) of plasma concentrations could reduce drug-related adverse events and improve clinical outcome in complex clinical conditions. Quantification of fosfomycin in plasma samples was performed by a rapid ultraperformance liquid chromatography mass spectrometry method. Sample preparation involved protein precipitation with [ 13 C3 ]-fosfomycin benzylamine salt as internal standard. The calibration curve ranged from 2 to 800 mg/L. Within- and between-day precision and accuracy, sensitivity, selectivity, dilution integrity, recovery were investigated and the results met the acceptance criteria. In patients, multiple drug dosing (every 6 or 8 hours) or in continuous administration were adopted, resulting in a large interpatient variability in drug concentrations (from 7.4 mg/L and 644.6 mg/L; CV: 91.1%). In critical care patient setting TDM can represent an important tool to identify the best fosfomycin dosing in single patients, taking into consideration clinical characteristics, infection sites and susceptibility of the treated pathogens.